Growth of Cross Contaminating Bacterial Pathogens in Fish Muscle at Different Temperatures of Storage - K.P., Nazeem Beena; K.G., Jeena; A.A., Mohamed Hatha (Fishery Technology, 2025)
Growth of cross contaminant bacterial pathogens such as enteropathogenic Escherichia coli (EPEC) and Salmonella typhimurium were examined in fish muscle maintained at 50C, 20oC and 350C to mimic the different conditions prevailing in the retail fish markets. While the cells hardly grew in fish muscle kept at 50C, there was 5 log and 4 log increase in number of cells of EPEC and S. typhimurium respectively at 350C. The growth of these cells at 20oC was more gradual and the increase in the number of cells was around 3 log. The results indicate potential danger posed by these contaminant bacterial pathogens to the consumers of temperature abused fish, which is a very common sight in the retail markets of India. Implementation of minimum standards for the fish markets, regular monitoring and enforcement are suggested to ensure food safety.